Varietal and time dependent differences in juglone and total phenolic contents of the walnut (Juglans regia L.) leaves - Kocaçalışkan, İsmail and Turan, Emel and Ertürk, Ümran and Demir, Yavuz and Terzi, İrfan (Progress in Nutrition, 2020)
From May to October, time dependent differences with two weeks intervals in juglone (5-Hydroxy- 1,4-naphthoquinon) and total phenolic content of the leaves of five walnut (Juglans regia L.) cultural varieties grown in Turkey (cv. Şebin, cv. Yalova-2, cv. Yalova-3, cv. Yalova-4 and cv. 1974/7) were investigated. Juglone and phenolic contents were determined by spectrophotometric methods. Correlations between juglonephenolic content, juglone-climatic factors and phenolic content-climatic factors were also established. In conclusion, there were significant differences between the varieties and the highest values of both juglone and phenolic content were recorded in Yalova-2 cultivar among the varieties. For example, maximum juglone content was determined in Yalova-2 (3,51 mg/g) but minimum in Yalova-4 (2,26 mg/g). Maximum phenolic content was also determined in Yalova-2 (51.8 mg/g), but minimum phenolic level was seen in 1974/7 cultivar (49,3 mg/g), as a mean. On the other hand, both juglone and phenolic content were generally higher from middle of August to middle of September and the lowest levels were seen in May. Further, while a significant positive correlation between juglone and phenolic contents of the leaves was found, there was almost no significant correlation between juglone and climatic factors except a significant negative correlation between phenolic content and wind speed in Yalova-2 cultivar.